Designing a participatory radio program to promote proper waste disposal and segregation in Brgy. Tacunan, Davao City - Galon, Jean Claire S.; Piala, Julius Neil A. (2019)
The study is centered on the designing of a participatory radio program to promote proper waste disposal and segregation in barangay Tacunan, Davao City for it is the most prominent problem in the community identified by the barangay council. Improper waste disposal and segregation had continued to thrive despite the efforts of the barangay in addressing the problem (e.g. barangay assemblies and purok consultations on the subject matter). The researcher, therefore, figured to address the problem by utilizing the established community audio tower of the barangay which is Radyo Tacunan. Radyo Tacunan was utilized because it has been proven an agent of unity and progress among the residents. To properly utilize Radyo Tacunan, the researcher did a formative research wherein she conducted key informant interviews with the purok leaders of the barangay and the DENR, and a focus group discussion with the Tacunan Young Broadcasters whom the researcher all figured to be the most credible resource persons for the study. The results of the formative research was analyzed though a thematic analysis and was later on used as a basis for the creation of the radio program. Upon the creation, the researcher conducted workshops with the barangay?s official broadcasting organization: the Tacunan Young Broadcasters, in which they started the story development and created the characters of the radio program with the barangay?s supervision. The finalized script was then recorded and was later on launched successfully in the barangay with the residents finding themselves listening to the produced radio program.
Thesis (BA Communication Arts) -- University of the Philippines Mindanao, 2019